Internal Psychological Resources and Professional Conduct in Policing: A Review of Psychological Capital Literature (2015-2025) - Iskandar, Eko; Wijoyo, Suparto; Suhariadi, Fendy (Technium Social Sciences Journal, 2026)
High operational pressure, unpredictable situations, and diverse public demands shape police officers’ daily work. These conditions create differences in psychological resilience and professional behaviour, even among officers performing similar duties. This study utilises the perspectives of Conservation of Resources (COR) Theory to examine how Psychological Capital (PsyCap) literature supports officers in managing stress, maintaining emotional stability, and making proportionate decisions in the field. Scopus-indexed articles published from 2015 to 2025 and classified as Q1-Q3 journals were reviewed. The findings indicate that PsyCap, encompassing hope, efficacy, resilience, and optimism, serves as a key internal resource, enabling officers to maintain adaptive performance under organizational and operational pressures. This study highlights that professionalism cannot rely solely on rules and hierarchy but must also be supported by strong psychological resources. Practically, this study recommends integrating PsyCap development into police training, supervision, and support systems to strengthen officers’ emotional control, responsiveness, and service quality.